2016
DOI: 10.1002/jgm.2883
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated artificial microRNA against human fibrinogen like protein 2 inhibits hepatocellular carcinoma growth

Abstract: HFGL2 might be a potential target for controlling angiogenesis in HCC and hfgl2 gene silencing via miRNA may be an alternative strategy for the management of HCC. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…These findings are supported by our observation that plasma sFGL2 levels are increased in patients with HCC compared to those without HCC and healthy controls. Either FGL2 knockdown or intratumoral injection of an artificial microRNA targeting hFGL2 leads to a delayed proliferation of tumor cells and an inhibition of tumor growth and angiogenesis as well as improves survival in vivo [ 33 , 38 , 39 ]. In addition, increased FGL2 expression is significantly associated with poor prognosis in patients with ccRCC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by our observation that plasma sFGL2 levels are increased in patients with HCC compared to those without HCC and healthy controls. Either FGL2 knockdown or intratumoral injection of an artificial microRNA targeting hFGL2 leads to a delayed proliferation of tumor cells and an inhibition of tumor growth and angiogenesis as well as improves survival in vivo [ 33 , 38 , 39 ]. In addition, increased FGL2 expression is significantly associated with poor prognosis in patients with ccRCC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGL2 is highly expressed in HCC tissues and contributes to HCC angiogenesis and hypercoagulability 31 . Moreover, FGL2 knockdown delays HCC growth and tumour angiogenesis 12 , 13 . Therefore, we speculate that FGL2 expression is highly associated with renal microthrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that FGL2 promotes angiogenesis and tumorigenesis in prostate cancer through FGF-2/ERK signalling 11 . Moreover, FGL2 promotes the growth and angiogenesis of human hepatocellular carcinoma (HCC) cells in mouse xenograft injected models 12 , 13 . FGL2 activity increases in B-cell lymphomas but decreases after remission; moreover, detection of FGL2 activity in peripheral blood mononuclear cells (PBMCs) could be a biomarker for B-cell lymphomas 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Interferons, GM-CSF, IL12, CD40L, CTLA4 [156][157][158][159][160][161][162][163][164][165][166][167][168]170] Nucleic-acid-based effectors. Liver detargeting, miR122, miR145, miR148, miR21, let7, KRAS, breast cancer, Hepatocellular carcinoma, colorectal cancer cells [202][203][204][205][206][207][208] c. Selective replication of virus in specific cells.…”
Section: Protein-based Effectorsmentioning
confidence: 99%